2020
DOI: 10.1007/s40864-020-00127-2
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Abandoned Railways Leads to Urban Regeneration: A Tale from a Rust Track to a Green Corridor in Zhangjiakou

Abstract: While high-speed train systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Other railway heritage recovery initiatives, such as those dedicated to buildings, locomotives and lines, have been built in Romania, Ethiopia and Taiwan. In some cases, the rolling stock was in good condition, while in others the interventions were carried out without in-depth technical knowledge [52][53][54][55].…”
Section: Rs1 What Are the Main Dynamics In The Recovery And Managemen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other railway heritage recovery initiatives, such as those dedicated to buildings, locomotives and lines, have been built in Romania, Ethiopia and Taiwan. In some cases, the rolling stock was in good condition, while in others the interventions were carried out without in-depth technical knowledge [52][53][54][55].…”
Section: Rs1 What Are the Main Dynamics In The Recovery And Managemen...mentioning
confidence: 99%
“…The results of the research on the Qinghai-Tibet railway have highlighted, on the one hand, the benefits to the local economy, thanks above all to tourists, while on the other hand, they have shown that the railway has caused an increase in human pressures on the mountain ecosystem [55,77].…”
Section: Rs3 What Are the Main Relationships Between Sustainability A...mentioning
confidence: 99%
“…Additionally to these results, in order to select the most suitable transformation mode for Guelma's station we had to go back to the several studies. In which were discussed the possibilities of three common strategies of reusing the abandoned railways: as a new transportation route, as a place for tourism and commerce and as a green corridor for the public (Zhang et al, 2020). Whilst converting into new rail transit systems will contribute to improve the public transport situation and increase land value.…”
Section: Level Of Information For Residentsmentioning
confidence: 99%
“…They have either been adapted to accommodate new needs of the cities (Jin & Wang, 2004) or, in many cases, have simply been abandoned if they did not fit into the new urban structure of the post-industrial city (Lin, 2018). These pieces of cities mark urban rupture areas resulting in a "rust belt" (Zhang et al, 2020). Are they a land of opportunity or burden inherited from the past?…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, the total mileage of China's subway network development will exceed 18,000 kilometres, and the subway has become the main mode of intra-city transport in large cities. In the construction process of urban rail transit engineering, track laying operations are required, which have factors such as long construction scope, large task volume, multiple processes, complex working conditions, and limited station operations [1]- [2] .At present, the industry generally adopts the installation of running rails for track laying in the track area, and the track laying machine uses the running rails for laying operations [3] .Although the existing trackless construction equipment can walk on the pipe wall through a specially designed running mechanism, has certain transformation functions, uses a new energy battery system to freely travel, and solve some of the shortcomings of traditional track laying machines, it has limitations in safety protection and universality [4]- [6] .In actual construction, there are many shortcomings in the existing track laying methods. Firstly, the method of laying the running track first not only causes great waste of human property, low efficiency, difficult operation, poor safety, but also easily damages the shield tunnel segments; Secondly, the existing trackless equipment has a low level of intelligence and a single function, which does not have deformation ability to adapt to multiple types of tunnel environments; In addition, the equipment is not flexible, resulting in high labor intensity among workers and significant safety hazards [7] .…”
Section: Introductionmentioning
confidence: 99%